2019
DOI: 10.3171/2018.2.jns172964
|View full text |Cite
|
Sign up to set email alerts
|

How to improve obliteration rates during volume-staged stereotactic radiosurgery for large arteriovenous malformations

Abstract: OBJECTIVE The management of large-volume arteriovenous malformations (AVMs) with stereotactic radiosurgery (SRS) remains challenging. The authors retrospectively tested the hypothesis that AVM obliteration rates can be improved by increasing the percentage volume of an AVM that receives a minimal threshold dose of radiation. METHODS In 1992, the authors prospectively began to stage anatomical components in order to deliver higher single doses to AVMs > 15 cm in volume. Since that time 60 patients with large AV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…This nding parallels the report of Kano et al who demonstrated that AVM obliteration results can be improved signi cantly when at least 63% of the AVM receives a dose >20 Gy; this also con rmed that margin dose critical predictor of successful obliteration. (23) Using the Gamma knife, we can increase the percent volume receiving higher dose by adding low weighted isocenters within the target volume while not changing the prescription margin dose or conformity. (23) Adverse radiation effect In a previous large SRS craniopharyngioma series, the rate of visual eld deterioration without tumor progression was 0-2.2% (4,5,7).…”
Section: Srs Conformity and Selectivity Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…This nding parallels the report of Kano et al who demonstrated that AVM obliteration results can be improved signi cantly when at least 63% of the AVM receives a dose >20 Gy; this also con rmed that margin dose critical predictor of successful obliteration. (23) Using the Gamma knife, we can increase the percent volume receiving higher dose by adding low weighted isocenters within the target volume while not changing the prescription margin dose or conformity. (23) Adverse radiation effect In a previous large SRS craniopharyngioma series, the rate of visual eld deterioration without tumor progression was 0-2.2% (4,5,7).…”
Section: Srs Conformity and Selectivity Conceptsmentioning
confidence: 99%
“…(23) Using the Gamma knife, we can increase the percent volume receiving higher dose by adding low weighted isocenters within the target volume while not changing the prescription margin dose or conformity. (23) Adverse radiation effect In a previous large SRS craniopharyngioma series, the rate of visual eld deterioration without tumor progression was 0-2.2% (4,5,7). In the present study, a single patient had visual eld deterioration unrelated to tumor progression.…”
Section: Srs Conformity and Selectivity Conceptsmentioning
confidence: 99%
“…Optimization of radiosurgical planning is important to improve the total obliteration rate while maintaining reasonable safety. For example, A recent study proposed that in addition to keeping a minimal margin dose of 17 Gy, increasing the percentage of the bAVM volume that receives at least 20 Gy treated in two stages could improve the outcome for large-volume bAVMs ( 302 ). What is more, a novel deep learning-based method to automatically segment the bAVM volume may be helpful for radiosurgical planning ( 303 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some reports noted a correlation between post-treatment brain radiation injury and the volume that received a specific dose, including surrounding structures other than the treated volume. Kano et al reported a correlation of 12 Gy-volume (the volume of tissue, including target, receiving >12 Gy) during GKRS for brain arteriovenous malformation (AVM) [24]. Korytko et al also reported a correlation of 12 Gy Volume and post-radiosurgical radionecrosis on imaging during GKRS for non-AVM intracranial tumors, including brain metastasis cases (53.5%= 92 / 198 cases) [25].…”
Section: Discussionmentioning
confidence: 99%